The Performance of Malaysian Unit Trusts Investing in Domestic Versus International Markets - Nur Atiqah Abdullah; Nur Adiana Hiau Abdullah (Asian Academy of Management Journal of Accounting and Finance, 2009)
This paper investigates the relationship between unit trusts invested domestically and those invested overseas. The performance of unit trusts investing overseas is compared to unit trusts that are invested locally to determine whether they outperform the local funds. The Kuala Lumpur Composite Index (KLCI) is used as the local funds’ benchmark. The Morgan Stanley Capital international All Country (MSCI AC) Asia Pacific and MSCI World Free are utilised as the international funds’ benchmarks. With a total of 26 local funds and 23 internationally invested funds, it is found that the risk-adjusted performance of internationally diversified funds is not significantly different from the performance of well-diversified domestic funds.